Particle swarm optimization based proportional-integral online-tuning by fuzzy logic controller (PSOFLC-PI) for cascaded multilevel inverter different load scenarios - Leong, Ying Foo; Nur Huda, Ramlan; Suliana, Ab Ghani; Hamdan, Daniyal (IEEE, 2025)
This research focuses on the 5-level cascaded H-bridge multilevel inverter (CHMI), utilizing a proposed controller known as PSOFLC-PI. The exact management of the multilevel inverter's (MLI) output voltage during load changes while satisfying the voltage harmonic and transition requirements—the voltage limit suggested by IEC and THD by IEEE—is the difficulty this study attempts to address. To solve this problem, PSO and FLC are integrated to ensure accurate and steady output voltage regulation while dynamically adjusting the controller in real-time tuning. MATLAB/Simulink is used to build and simulate the suggested controller, and under different load scenarios, its performance is contrasted with that of traditional PI and PSO-based PI controllers. In a variety of load scenarios, such as nominal load, no load to full load, and nonlinear load, the findings show that the PSOFLC-PI controller greatly improves output voltage regulation, reaching the intended peak voltage, minimal THD and satisfactory settling time.